(untitled) - Zuboff, Shoshana (New York, 1988)
Contents: Dilemmas of transformation in the age of the smart machine; Knowledge and computer-mediated Work; The abstraction of industrial work; The abstraction of industrial work; The dominion of the smart machine...
Keywords: Automation,Tự động hóa; Economic aspects,Khía cạnh kinh tế